40 Agile Methods in 40 Minutes - Smith, Craig (Scrum Australia 2014, 2014)
My presentation from Scrum Australia 2014 called “40 Agile Methods in 40 Minutes” is available on Slideshare. With 73% of the world using Scrum as their predominant Agile method, this session will …